The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26216526
|View full text |Cite
|
Sign up to set email alerts
|

Facile Construction of Bio-Based Supramolecular Hydrogels from Dehydroabietic Acid with a Tricyclic Hydrophenanthrene Skeleton and Stabilized Gel Emulsions

Abstract: Supramolecular hydrogels have attracted great attention due to their special properties. In this research, bio-based supramolecular hydrogels were conveniently constructed by heating and ultrasounding two components of dehydroabietic acid with a rigid tricyclic hydrophenanthrene skeleton and morpholine. The microstructures and properties of hydrogels were investigated by DSC, rheology, SAXS, CD spectroscopy, and cryo-TEM, respectively. The critical gel concentration (CGC) of the hydrogel was 0.3 mol·L−1 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…In our previous work, we reported the facile construction of bio-based supramolecular hydrogels from dehydroabietic acid for forming gel emulsions. 34 However, rosin-based supramolecular metallohydrogels and their applications in dye adsorption species have not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we reported the facile construction of bio-based supramolecular hydrogels from dehydroabietic acid for forming gel emulsions. 34 However, rosin-based supramolecular metallohydrogels and their applications in dye adsorption species have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Song reported that an amphiphilic hydrogelator was derived from dehydroabietic acid with an oxidized amine structure and application to the preparation of gel emulsions. In our previous work, we reported the facile construction of bio-based supramolecular hydrogels from dehydroabietic acid for forming gel emulsions . However, rosin-based supramolecular metallohydrogels and their applications in dye adsorption species have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These products are introduced into polymer chains to obtain network polymers with good mechanical properties and homogeneous structures. At present, the main research on rosin in the field of polymer materials includes the fabrication of light-controllable amphiphilic polymers [19], polyurethane microspheres [20,21], antibacterial coatings [22], marine antifouling coatings [23], and supramolecular hydrogels [24]. As a renewable biomass resource, rosin and its derivatives have significant research potential and application prospects in the fabrication of polymeric self-healing materials.…”
Section: Introductionmentioning
confidence: 99%